Lower Blood Pressure After Transcatheter or Surgical Aortic Valve Replacement is Associated with Increased Mortality - Lindman, Brian R.; Goel, Kashish; Bermejo, Javier; Beckman, Joshua; O'Leary, Jared; Barker, Colin M.; Kaiser, Clayton; Cavalcante, João L.; Elmariah, Sammy; Huang, Jian; Hickey, Graeme L.; Adams, David H.; et al. (Journal of the American Heart Association, 2019)
Background Blood pressure (BP) guidelines for patients with aortic stenosis or a history of aortic stenosis treated with aortic valve replacement (AVR) match those in the general population, but this extrapolation may not be warranted. Methods and Results Among patients enrolled in the Medtronic intermediate, high, and extreme risk trials, we included those with a transcatheter AVR (n=1794) or surgical AVR (n=1103) who were alive at 30 days. The associations between early (average of discharge and 30 day post-AVR) systolic BP (SBP) and diastolic BP (DBP) measurements and clinical outcomes between 30 days and 1 year were evaluated. Among 2897 patients, after adjustment, spline curves demonstrated an association between lower SBP (<120 mm Hg, representing 21% of patients) and DBP (<60 mm Hg, representing 30% of patients) and increased all-cause and cardiovascular mortality and repeat hospitalization. These relationships were unchanged when patients with moderate-to-severe aortic regurgitation post-AVR were excluded. After adjustment, compared with DBP 60 to <80 mm Hg, DBP 30 to <60 mm Hg was associated with increased all-cause (adjusted hazard ratio 1.62, 95% CI 1.23-2.14) and cardiovascular mortality (adjusted hazard ratio 2.13, 95% CI 1.52-3.00), but DBP 80 to <100 mm Hg was not. Similarly, after adjustment, compared with SBP 120 to <150 mm Hg, SBP 90 to <120 mm Hg was associated with increased all-cause (adjusted hazard ratio 1.63, 95% CI 1.21-2.21) and cardiovascular mortality (adjusted hazard ratio 1.81, 95% CI 1.25-2.61), but SBP 150 to <180 mm Hg was not. Conclusions Lower BP in the first month after transcatheter AVR or surgical AVR is common and associated with increased mortality and repeat hospitalization. Clarifying optimal BP targets in these patients ought to be a priority and may improve patient outcomes. Clinical Trial Registration Information URL: http://www.clinicaltrials.gov. Unique identifiers: NCT01586910, NCT01240902.